EVALUASI TATA KELOLA TEKNOLOGI INFORMASI DENGAN FRAMEWORK COBIT 5 DI BANK SUMSEL BABEL CABANG INDRALAYA - Fajar Prayoga; Widya Cholil; Tata Sutabri; Tri Basuki Kurniawan (P3M Institut Teknologi Pagar Alam, 2023)
Bank Sumsel Babel is one of the banks in Indonesia with the company name PT Regional Development Bank of South Sumatra and Bangka Belitung. Bank Sumsel Babel is also a Regionally Owned Commercial Bank (BUMD) which has many branch offices, one of which is Bank Sumsel Babel Indralaya Branch. Currently, Bank Sumsel Babel, Indralaya Branch, in governance or governance of IT (Information Technology) processes have not been fully implemented. Evaluation of information technology governance needs to be carried out to determine the level of success or progress of IT and measure whether the existing IT at Bank Sumsel Babel Indralaya is used effectively and efficiently. The processes used in this study are EDM03, EDM04, APO01, APO02, APO06, APO07, DSS01, DSS03, and MEA01. The maturity level is used to see an overview of the current state of information technology governance and future improvements so as to produce an IT Governance recommendation. which is the development of IT Governance that has been implemented by Bank Sumsel Babel Indralaya at this time. From the mapping of the maturity model, it will be obtained what level is the maturity level of Sumsel Babel Indralaya, so that the maturity of each control process can be even better to support the achievement of IT management objectives carried out on maximum point.